2004
DOI: 10.1111/j.1365-2036.2004.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Helicobacter pylori and its eradication on gastro‐oesophageal reflux disease in patients with duodenal ulcers or reflux oesophagitis

Abstract: SUMMARYBackground: The effect of Helicobacter pylori in provoking or protecting against gastro-oesophageal reflux disease is unclear and studies have given conflicting results. Recent guidelines recommend H. pylori eradication in patients on long-term proton pump inhibitors. Aim: To ascertain the effect of H. pylori eradication on gastro-oesophageal reflux disease outcomes (reflux oesophagitis and heartburn) in patients with duodenal ulcer disease, and to ascertain the effect of H. pylori infection on reflux o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 51 publications
5
53
0
11
Order By: Relevance
“…6,19,31 A recent systematic review did not find any significant differences between H. pylori positive and negative GERD patients in respect of healing rates, time to relapse, ph values and recurrence of symptoms. 32 However, our finding is consistent with a subsequent trial of H. pylori positive patients from this cohort, where eradication reduced overall dyspepsia scores (measured by the LDQ), but not reflux scores (measured by the CDRQ) and consequently, reflux was more likely to be the residual predominant symptom. 8 Helicobacter pylori negative patients may have worse oesophagitis than those who are H. pylori positive 33,34 and this may be especially important in relation to cagA status.…”
Section: Discussionsupporting
confidence: 91%
“…6,19,31 A recent systematic review did not find any significant differences between H. pylori positive and negative GERD patients in respect of healing rates, time to relapse, ph values and recurrence of symptoms. 32 However, our finding is consistent with a subsequent trial of H. pylori positive patients from this cohort, where eradication reduced overall dyspepsia scores (measured by the LDQ), but not reflux scores (measured by the CDRQ) and consequently, reflux was more likely to be the residual predominant symptom. 8 Helicobacter pylori negative patients may have worse oesophagitis than those who are H. pylori positive 33,34 and this may be especially important in relation to cagA status.…”
Section: Discussionsupporting
confidence: 91%
“…(24). Similar conclusions were drawn in a systematic review, which found no evidence that H. pylori eradication in patients with DU might provoke refl ux esophagitis (25). Pathophysiologically, most of the DU cases are associated with antrum-predominant H. pylori gastritis with increased gastric acid secretion; therefore, such patients might be at increased risk for developing GERD and DU, and both conditions might improve after H. pylori eradication (11).…”
Section: Discussionsupporting
confidence: 57%
“…A systematic review of 27 published studies concluded that eradication of H. pylori infection from patients with duodenal ulcer did not predispose to the development of GERD ( 49 ) or worsen symptoms in patients with established GERD ( 49 ).…”
Section: Gastroesophageal Refl Ux Disease (Gerd)mentioning
confidence: 99%